Rancang Bangun Aplikasi Sistem Inventory dengan Barcode di Laboratorium Teknik Elektro Universitas Bangka Belitung - Asmar Asmar; Ghiri Basuki Putra (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2021)
The laboratory is a place for students to carry out practicum activities to better understand a subject. In the UBB Electrical Engineering laboratory, a lot of electronic tools and components are used so that an inventory of the equipment and components is needed so that they are easy to use. Previously, the inventory of goods at the Electrical Engineering Laboratory used a manual recording system so that its implementation was not running optimally and was still manual so that many problems occurred. To overcome this, an application is needed that is able to record equipment and components in the laboratory, the borrowing process, returns and the condition of existing goods automatically. This inventory application is made through several stages, namely, problem identification, design, application development and tool barcobe and application implementation stage. The application is made using data processing software, while the barcode is made using Barcode Studio. The results of this study have been applied to the Electrical Engineering Laboratory and are very helpful in the process of borrowing, returning, controlling the condition of existing goods in the laboratory, and making reports and can be done digitally and data storage becomes safer and electronic.